Comparison of Islamic Education in Indonesia and Malaysia - Tyas Kubana Vitaloka; Sahda Nastiti Mufidah (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
Islamic education is not only aimed at providing an understanding of theory and religious teachings, but also at building mental attitudes as realized in good deeds. Islamic education is an attempt to improve the quality of morals and social characters. It also plays a major role in determining the quality of a nation and directing people to have good attitudes and characters, imbued by spiritual values. In Indonesia and Malaysia, Islamic education initially emerged along with the arrival and spread of Islam on both countries. Although both are countries with the majority of Muslims in Southeast Asia and have undergone several phases including against colonialism, the dynamics of Islamic education in those countries are not necessarily the same. The present study discusses the Islamic education in Indonesia and Malaysia, ranging from the history of the arrival of Islam to the initial and development of Islamic education that still evolves until today